KONSEP SAHABAT MENURUT MAḤFŪẒ AL-TARMASĪ (1842-1920 M) - Anshori, Muhammad (IAIN Kediri, 2017)
This article tries to explore the concept of shahabat in a book Manhaj Żawīal-Naẓar written by Maḥfūẓ al- Tarmasī. This book is Sharḥ Naẓm Alfīyah al-Suyūṭī (died in 911 H) consisting of 980 stanzas, and is added 20 stanzas by al-Tarmasī, so the total is 1000 stanzas. One of the interesting point to be discussed in hadith study is the concept of shahabat, the first source of hadith. The validity of shahabat becomes polemic between Sunni and Shi’i, especially on the concept of shahabat justice. In the book, there is no new concept of shahabat’s justice in general. Al- Tarmasī only repeats the previous ulama’s explanations in his book. By following the majority of ulama, he states that all shahabat are ādil (fair), but the reality shows that not all of them are ādil (fair). This article has been proved it by quoting some sources. Modern Muslim scholars also ask about the concept of al-ṣaḥābah kulluhum udūl. In some literatures, it has been mentioned some shahabat’s attitudes that did not show the Islamic values. There are many examples of bad shahabat’s behavior, so it can be said that the concept of al-ṣaḥābah kulluhum udūl does not have to be understood that all shahabat are ādil (fair). The appropriate meaning is that some of shahabat are ādil (fair) since “kullu” here is juz’iyah (some), not kulliyah (whole). Keywords: ādil, Maḥfūẓ al-Tarmasī, Manhaj Żawīal-Naẓar, Sahabat